2010
DOI: 10.1111/j.1540-8159.2010.02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Tramadol Overdose Associated with Brugada ECG Pattern

Abstract: Tramadol is a commonly prescribed synthetic opioid analgesic. In humans, electrocardiogram (ECG) changes consistent with sodium-channel blockade have not been described in overdoses with tramadol. We report a case of isolated tramadol overdose associated with a Brugada ECG pattern. A review of the literature reveals no previous human cases of tramadol overdose causing ECG changes consistent with sodium-channel blockade. However, in vitro blockade of sodium-channels has been demonstrated with high concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…In majority of toxicities, no arrhythmia was reported except to tachycardia 8 . There are a few case reports of Brugada ECG pattern, right-sided heart failure (HF), refractory shock, and asystole 12, 13, 14. Interestingly, hypertension is seen in some cases 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In majority of toxicities, no arrhythmia was reported except to tachycardia 8 . There are a few case reports of Brugada ECG pattern, right-sided heart failure (HF), refractory shock, and asystole 12, 13, 14. Interestingly, hypertension is seen in some cases 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Nausea/vomiting and respiratory depression have also been reported 5, 7, 8. Of cardiac issues, hypotension, especially affecting systolic blood pressure (SBP) and sinus tachycardia have been listed as tramadol toxicity complications 5, 7, 8, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…The unmasking of the Brugada pattern (often provoked with agents such as cocaine, propofol, tricyclic antidepressants, anesthetics, antiarrhythmic medications, as well as fever or electrolyte imbalance) has been highly-associated with risk for malignant arrhythmias and cardiac arrest [13]. The appearance of a Brugada pattern has been reported in the context of opiate use, such as methadone ingestion and tramadol overdose in previously-published cases [14,15]. The observation of QRS prolongation and Brugada pattern with high serum loperamide concentration suggests potential of sodium channel blockade in a manner similar to Class I antiarrhythmic medications.…”
Section: Discussionmentioning
confidence: 99%
“…6 Cole et al reported an asymptomatic Brugada-like ECG pattern associated with isolated tramadol overdose. 7 Authors hypothesize that tramadol blockade of sodium channels might be the cause of observed ECG changes.…”
Section: Discussionmentioning
confidence: 99%